Qualitative Research: Teachers' Impact on Graduates' Employability Quality: Penelitian Kualitatif: Dampak Guru terhadap Kualitas Kesiapan Kerja Lulusan - Sumantrie, Pipin; Limbong, Martalina; Purba, Yunis Veronika; Silaban, Cesarina; Manalu, Jespin Saurlina (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Early childhood is a critical phase for developing social competencies such as empathy, cooperation, and communication. Specific Background: In the digital era, millennial parents adopt teach free parenting, a flexible and communicative approach that allows children to learn through experience within guided boundaries. Knowledge Gap: Empirical evidence on how this parenting model is implemented and its role in early childhood social development in Indonesia remains limited. Aims: This study aims to describe the implementation of teach free parenting by millennial parents and examine its role in children’s social development in Lamongan kindergartens. Results: Using a qualitative case study with interviews involving parents and teachers, findings show that this approach balances autonomy and parental guidance, fostering confidence, empathy, cooperation, and communication skills through open interaction and consistent support. Challenges include environmental factors, gadget use, and differences in family parenting, while collaboration between parents and schools supports its application. Novelty: The study presents teach free parenting as an adaptive form of democratic parenting in the digital context. Implications: The findings provide practical guidance for parents and educators in applying adaptive parenting to support children’s social development. Highlights• Flexible caregiving approach balances autonomy with structured guidance• Social competencies emerge through dialogue and experiential learning• Parent–school synergy supports consistent developmental processes KeywordsTeach Free Parenting; Millennial Parents; Early Childhood; Social Development; Democratic Parenting